2010
DOI: 10.1262/jrd.10-010t
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fetal Sex by Amplification of Fetal DNA Present in Cow Plasma

Abstract: Abstract. The aim of the present study was to predict fetal sex at different time points of gestation in cattle by detecting the fetal SRY gene in cow plasma. Plasma DNA was extracted from the blood samples of 110 pregnant cows during the gestational period of 30 to 242 days. Nested PCR was employed to detect the fetal SRY, which the male fetus carries exclusively, in cow plasma. The cows positive for SRY were predicted to carry male fetuses. The results showed that the fetal DNA from cow plasma was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
4
10
0
2
Order By: Relevance
“…In pregnant mice, Khosrotehrani et al [29] described an increase in cell-free fetal DNA levels during each of the 3 weeks of gestation. Wang et al [30] reported the presence of cell-free fetal DNA in the plasma from pregnant cows, and de Leon et al [31] made similar observations in pregnant horses. In pregnant sheep, Kadivar et al [32] detected a 1.65-fold increase in maternal plasma cell-free fetal DNA levels for the last two months of gestation compared to the middle months.…”
Section: Resultsmentioning
confidence: 88%
“…In pregnant mice, Khosrotehrani et al [29] described an increase in cell-free fetal DNA levels during each of the 3 weeks of gestation. Wang et al [30] reported the presence of cell-free fetal DNA in the plasma from pregnant cows, and de Leon et al [31] made similar observations in pregnant horses. In pregnant sheep, Kadivar et al [32] detected a 1.65-fold increase in maternal plasma cell-free fetal DNA levels for the last two months of gestation compared to the middle months.…”
Section: Resultsmentioning
confidence: 88%
“…Intron-containing pseudogenes have also been reported for TSPY (known as TSPY-C ) [Verkaar et al, 2004] so to avoid amplification of these pseudogenes, the genomic primers used in this study were designed in regions of low sequence similarity between TSPY-C and TSPY . The sex-determining region, SRY , was selected as a single copy Ychromosomal reference gene [Chandler et al, 2007], using primer sets SRY-1 [Hamilton et al, 2009] and SRY-2 [Wang et al, 2010] for trials #1 and #2, respectively.…”
Section: Gene Selection and Primer Designmentioning
confidence: 99%
“…Currently, there are at least four approaches to sex determination in ruminant species, based on the onset of development: a) artificial insemination using flow cytometry sexsorted semen (De Vries et al, 2008); b) polymerase chain reaction (PCR)-based detection of gender-specific sequences in preimplantation embryos prior to embryo transfer Tsai et al, 2011); c) ultrasound fetal scanning of pregnant females in early pregnancy (Hughes and Davies, 1989;Davis and Haibel, 1993); and d) fetal DNA detection in the blood/serum of pregnant females (Wang et al, 2010;Kadivar et al, 2013). Each approach has its technical and economic advantages but also its limitations, and the choice of a particular procedure may depend on many factors.…”
Section: Introductionmentioning
confidence: 99%